Optimising Children's Readiness to Learn through Mediating Social Disadvantage: Exploring Models of Best Practice. Issue 2 (May 2015) - Targowska, Anna; Teather, Susan; Guilfoyle, Andrew
THIS ARTICLE DISCUSSES THE importance of early support for families in increasing their children's readiness to learn and optimising their developmental outcomes. It reports the findings of the evaluation of the It Takes a Village: Multicultural Early Learning Program, a research project undertaken in 2009–2011 by a research team from Edith Cowan University, Western Australia. The unique model and characteristics of the program are discussed in the context of its role in facilitating children's developmental potential, through the mediation of social disadvantage of the new migrant and humanitarian entrant families in the south-east corridor of Perth's metropolitan area.